Ivermectin 1%. Field trial on ovine psoroptic mange (Semiárida, 2020)
How to check, in field conditions the acaricide action of Ivermectina 1% of Psoroptes comunis var. ovis; 47 sheep of different age, weight and both sexes, presenting a high degree of parasite infestation and with large injured body areas, 36 were medicated on three different levels of dosage, as follow: 300 mcg/KPV single dose, 600 mcg/KPV single dose and 300 mcg/KPV double dose, administered in two doses given with 10 days’ interval 11 sheep were untreated control. From the three levels tested the second proved to be the most effective: 600 mcg/KPV single dose, subcutaneous in the interthight. The double dose was also effective but the animals treated were more sensitive to relapses during the development of the experience. It should be noted the acaricide effect of the product, the absence side effects and the ease of administration just as the disadvantages for medicating it accurately. In spite of effectiveness checked, it should not be overlooked the necessary precautions for avoiding relapses and/or new parasitic infestations.
Keywords: Sheep